Mechanism of water vapor transport through PET/AlOxNy gas barrier films - Erlat, A; Henry, B; Grovenor, C; Briggs, G; Chater, R; Tsukahara, Y (2004)
Thin, transparent aluminum oxide coatings on polymers are used widely to improve the gas barrier properties of commodity polymers in the food packaging, pharmaceutical, and organic display technologies. Recently we introduced reactively sputtered aluminum oxynitride coatings on poly (ethylene terephthalate) as a novel alternative to oxide coatings and have shown that they possess, in particular, superior water vapor permeation resistance. In this paper we give a detailed account of how altering the oxynitride morphology and chemistry by varying the magnetron sputtering conditions can directly alter the water vapor barrier performance but has little effect on oxygen permeation. Analysis of these films has also been extended to comparisons with titanium oxynitride and aluminum oxide layers on polymer substrates. In addition to gas permeation measurements and activation energy calculations, a variety of techniques such as atomic force microscopy, scanning electron microscopy, X-ray photoelectron spectroscopy, Rutherford backscattering, and secondary ion mass spectroscopy have been used to correlate the barrier performance to the morphology and chemistry of the films in a more complete model for water vapor permeation.